Pengembangan Literasi Digital Guru dan Siswa Melalui Program Kampus Mengajar di SMPN 19 Mataram - Hikmawati Hikmawati; Kadek Indah Widya Sari; Maziya Malkan; Talitha Gita Andani; Faradilla Ngesti Habibah (Pascasarjana Universitas Mataram, 2021)
The basic literacy that must be possessed by someone to be able to compete in the 21st century is literacy, numeric literacy, scientific literacy, digital literacy, financial literacy, and cultural and civic literacy. This community service activity aims to develop digital literacy for teachers and students through the Teaching Campus program at SMPN 19 Mataram. The Teaching Campus Program is one of the implementations of the Independent Campus Policy which is beneficial for students. This community service activity at SMPN 19 Mataram was carried out from August 4, 2021 to September 25, 2021. The method of activity consisted of four stages each week, namely: planning weekly activities with the team, carrying out weekly activity plans, analyzing weekly activities, making improvement plans and follow-up. The form of digital literacy development activities is that students help teachers and students in implementing technology, information and communication (ICT) based learning. Students help teachers and students in optimizing the use of various digital applications, namely WhatsApp, Zoom Meeting, Google Meet, Google Drive, and Google Form. Students also assist teachers in preparing teaching materials in the form of power point media (ppt) and learning videos. Thus, the Campus Teaching program is beneficial for students to gain hands-on experience in the field of becoming professional teachers, teachers and students also gain information and skills in using various digital technologies as a provision to face global competition in the 21st century